(3efJNH cfR GdYeGds - (3CHh GdWGgQ eMeO Hf EHQGgje Hf MSf GdchQGfi GdcQOi GdTgQRhOis; (3Ydj Hf YHO Gdedc MSGe GdOjf GHf bGVj NGf GdbGOQj GdTGPdj GdgfOj Ke GdeOfj aGdecj, YdGA GdOjf GdTgjQ H` GdeJbj,J (B975 (3g` s
(3ChdgG (B:s
(3GdebUO GdChd ai Ndb GdYGde cd TF Ndb ef GdeGA Me cQ s
(3BNQgG (B:s
(3jJRQhf CHh HcQ hYeQh YKeGf GHf SYO Yf EHQGgje CHj YeQ GdOQGei bGd UGMH GdCUd (B: (3gPG BNQ cJGH efJNH Sff GdGbhGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B309 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B59 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B746s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B1114s
Keywords: (3GdMOjK h GdeUWdMs